Allelic polymorphism and inheritance of MdACS1 and MdACO1 genes in apple (Malus × domestica Borkh.). Issue 1 (5th December 2013) - Marić, Slađana; Lukić, Milan; Flachowsky, H.
Abstract The allelic polymorphism and inheritance of MdACS1 and MdACO1 genes were analysed in 28 apple cultivars, which were derived from reciprocal crosses of the following parental pairs: 'Golden Delicious' × 'James Grieve', 'Golden Delicious' × 'Jonathan', 'Cox's Orange Pippin' × 'Golden Delicious', 'Cox's Orange Pippin' × 'Jonathan'. Polymorphisms were detected by PCR and the use of two restriction enzymes (BamH1 and RsaI). In addition, new primers were designed for the further discrimination of MdACO1 alleles. Two alleles of MdACS1 gene (MdACS1‐1 and MdACS1‐2) and three alleles of MdACO1 gene (a, b and c) were detected. Cloning and sequencing of MdACO1 alleles confirmed a high conservation and some differences within the coding regions and helped to reconcile between different numbering systems. Observed segregations confirmed that alleles a, b and c belonged to the MdACO1 gene. It is apparent that polymorphisms within the MdACS1 and MdACO1 genes could aid cultivar genotyping and identification and, furthermore, that the MdACS1‐2/2 genotype is correlated with a long apple storage life.